The nucleolus - Olson, Mark O. J.; SpringerLink (Online service). (New York, NY Springer New York, 2011)
Within the past two decades, extraordinary new functions for the nucleolus have begun to appear, giving the field a new vitality and generating renewed excitement and interest.  These new discoveries include not only the novel functions of the nucleouls, but also numerous breakthroughs on its conventional role.  Consequently, a large part of this volume is devoted to traditional functions of the nucleolus.  Recent research has led to so much information that the subject cannot be fully contained within one volume, so this book has focused on recent progress in specialized topics within the general subject. The Nucleolus is divided into three parts: nucleolar structure and organization, the role of the nucleolus in ribosome biogenesis, and novel functions of the nucleolus.  Proteomics has shown that there are hundreds of proteins of unknown function in the nucleolus, which are likely to keep researchers busy for years.  In addition, the roles of many viral components in the nucleolus will continue to intrigue us, hopefully moving beyond the phenomenology that is now the case with many viral components in the nucleolus.  Even now, there is already evidence that we can take advantage of our knowledge of the nucleolus to develop therapeutic strategies, and this book hopes to help build the path to a new era of nucleolar translational medical research.
Nucleolar Structure and Organization.Structural organization of the nucleolus as a consequence of the dynamics of ribosome biogenesis.The dynamic  proteome of the nucleolus.The Structure of rDNA Chromatin.The epigenetics of the nucleolus: structure and function of active and silent ribosomal RNA genes.UBF, an Essential Player in Maintenance of Active NORs and nucleolar formation -- Role of the Nucleolus in Ribosome Biogenesis.The RNA Polymerase I Transcription Machinery.Small Ribonucleoproteins in Ribosome Biogenesis.Crosstalk between ribosome synthesis and cell cycle progression and its potential implications in  human genetic disease.The multiple properties and functions of nucleolin.The multifunctional nucleolar protein nucleophosmin/NPM/B23 and the nucleoplasmin family of proteins.Structure and function of NOPP140 and treacle -- Novel Functions of the Nucleolus.The Role of the Nucleolus in the Stress Response.New Frontiers in Nucleolar Research - Nucleostemin and Related Proteins.Viruses and the Nucleolus.Assembly of Signal Recognition Particles in the Nucleolus.Relationship of the Cajal Body to the Nucleolus.Role of the Nucleolus in HIV Infection and Therapy.
Electronic reproduction.
Keywords: Nucleolus; Drug delivery systems; Electronic books